Effects of localized and general fatigue on static and dynamic postural control in male team handball athletes - Zech, A.; Steib, S.; Hentschke, C.; Eckhardt, H.; Pfeifer, K. (The Journal of Strength and Conditioning Research, 2012)
In team sports, sensorimotor impairments resulting from previous injuries or muscular fatigue have been suggested to be factors contributing to an increased injury risk. Although it has been widely shown that physical fatigue affects static postural sway, it is still questionable as to what extent these adaptations are relevant for dynamic, sports-related situations. The objective of this study was to determine the effects of whole-body and localized fatigue on postural control in stable and unstable conditions. Nineteen male team handball players were assessed in 2 sessions separated by 1 week. Treadmill running and single-leg step-up exercises were used to induce physical fatigue. The main outcome measures were center of pressure (COP) sway velocity during a single-leg stance on a force plate and maximum reach distances of the star excursion balance test (SEBT). The COP sway velocity increased significantly (p < 0.05) after general (+47%) and localized fatigue (+10%). No fatigue effects were found for the SEBT. There were no significant correlations between COP sway velocity and SEBT mean reach in any condition. The results showed that although fatigue affects static postural control, sensorimotor mechanisms responsible for regaining dynamic balance in healthy athletes seem to remain predominantly intact. Thus, our data indicate that the exclusive use of static postural sway measures might not be sufficient to allow conclusive statements regarding sensorimotor control in the noninjured athlete population.